2014
DOI: 10.1007/s12598-014-0273-8
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and phase transformation behavior of Mo–MoSi2 gradient material

Abstract: Mo-MoSi 2 gradient coating on Mo substrate was prepared by siliconizing process, using the polysilicon as silicon atoms. The gradient layer was analyzed by the experimental results, theoretical analysis, and thermodynamic calculation. The silicon, molybdenum content of gradient coating shows a gradual change regulation. The reaction between silicon and molybdenum is most likely to generate Mo 5 Si 3 , then MoSi 2 , finally Mo 3 Si, but when the silicon content is excessive, the Mo 5 Si 3 and Mo 3 Si will react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The authors documented that functionally graded MoSi2-Mo coatings produced by the proposed method show an excellent oxidation resistance and a good bonding with Mo substrates. They also observed that the morphology of MoSi2-Mo products might be also easily controlled by adjusting the hot-dipping process parameters [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The authors documented that functionally graded MoSi2-Mo coatings produced by the proposed method show an excellent oxidation resistance and a good bonding with Mo substrates. They also observed that the morphology of MoSi2-Mo products might be also easily controlled by adjusting the hot-dipping process parameters [17,18].…”
Section: Introductionmentioning
confidence: 99%